Direct aortic TAVI via anterior right mini-thoracotomy using 32 mm myval for pure aortic regurgitation - Firas Aljanadi; Graham McNeilly; Ganesh Manoharan; Andrew McNiece; Reuben Jeganathan (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Aortic regurgitation with dilated annulus presents a technical challenge for conventional transcatheter aortic valve implantation (TAVI) procedures. Case presentation We report a case of an 84-year-old frail patient with a history of breathlessness found to have severe aortic regurgitation and moderately impaired left ventricular systolic function. The patient underwent a successful TAVI procedure using the XL-Myval 32 mm transcatheter heart valve (THV) via an anterior right mini-thoracotomy with a direct aortic approach. The patient recovered well post-operatively with good hemodynamic resolution. Conclusions This first in human case highlights the efficacy and potential of applying innovative approaches, such as the new sizes of Myval THV and direct aortic access via anterior right mini thoracotomy, in addressing challenging anatomical variations in TAVI procedures with good outcome.